Ultra-processed foods as a possible culprit for the rising prevalence of inflammatory bowel diseases - Vissers, Eva; Wellens, Judith; Sabino, João (Frontiers in Medicine, 2022)
Inflammatory bowel diseases (IBD) are chronic inflammatory disorders of the gastrointestinal tract, and the exact pathogenesis is still unclear. It is believed that IBD develops in response to a complex interaction between the microbiota, environmental factors, and the immune system, in genetically predisposed individuals. Identifying these environmental factors will offer more insight in the development of the disease, and reveal new therapeutic targets for IBD patients. One of the environmental factors that has gained more interest over the last years is our diet. The prevalence of IBD has increased significantly and this increase is thought to be associated with a ‘Western diet’, characterized by high intake of fats, added sugar, meat, and ultra-processed foods (UPFs). The UPFs now account for almost 50% of the energy intake in Westernized countries and are therefore an important characteristic of this Western diet. UPFs are characterized by higher amounts of salt, fat, sugar and the presence of different food additives. Epidemiological studies have found associations between UPF intake and a range of non-communicable diseases, including inflammatory bowel disease (IBD). Preclinical and clinical evidence suggest that non-nutritive ingredients and additives, present in UPFs, can negatively affect different components of the intestinal barrier, such as the microbiota, the mucus layer, the epithelium, and the immune cells in the lamina propria. Disruption of this barrier can cause the immune system to encounter an increased bacterial exposure, leading to an aberrant immune response. In this article, the available evidence on the possible role of UPFs and their components in the increasing incidence and prevalence of IBD is reviewed. These findings can be translated to the clinic and may be helpful to consider when giving dietary advice to IBD patients. A better understanding of the role of UPFs may lead to less restrictive diets for patients with IBD, hence increasing the dietary compliance and efficacy of exclusion diets.